A blue transformation for global One Health - Stentiford, Grant David; Bremner, Julie; Bass, David (Frontiers in Aquaculture, 2025)
Global per capita consumption of aquatic foods has never been higher, though significant differences between nations exist. The nutritional benefits of consuming aquatic foods, their wider role in food security, and the potentially lower food safety risks of consumption compared to other meats—combined with their lower environmental footprints—deliver One Health benefits as part of a so-called “blue transformation.” Whilst this is intuitive and correct, it can only be achieved by protecting and enhancing water quality in our rivers, seas, and oceans; by mitigating the negative impacts of climate change in locations where aquatic production occurs; and by ensuring that poor animal health does not catalyse overuse of antimicrobial agents, which subsequently threaten human, animal, and environmental health.